On Pyrometry in Particulate-Generating Flames. Issue 9 (4th July 2022) - De Iuliis, Silvana; Dondè, Roberto; Altman, Igor
ABSTRACT: Pyrometry is a common tool to measure temperature and concentration of particles present in flame. It is essentially based on the measurement of light emission from flame-generated particulate assumed to be in equilibrium with the gas. In the present work the existing evidence of non-isothermality, which is the coexistence of hot and cold particles in the probe volume, is analyzed and its effect on the pyrometry measurements is considered. Light emission from titania nanoparticles produced in a flame spray is compared with that obtained irradiating the flame with a pulsed laser. The effect of the heating process on temperature and particle concentration measurements allows one to prove the coexistence of hot and cold particles in the flame before the irradiation. In order to interpret the experimental results, a thought experiment is performed to model the possible occurrence of different percentages of particles with varying temperature. The general implications to the pyrometry measurements in flames are also discussed.